Review : Seed Treatments Using Matriconditioning to Improve Vegetable Seed Quality - Satriyas Ilyas (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2006)
-